Systemic Inflammation and Cardiovascular Comorbidity in Psoriasis Patients: Causes and Consequences - Boehncke, Wolf-Henning (Frontiers in Immunology, 2018)
Psoriasis is a common inflammatory skin disease characterized by the appearance of red scaly plaques that can affect any part of the body. High prevalence, chronicity, disfiguration, disability, and associated comorbidity make it a challenge for clinicians of multiple specialties. Likewise, its complex pathogenesis, comprising inflammation, hyperproliferation, and angioneogenesis, intrigues numerous scientific disciplines, namely immunology. From a clinical perspective, the severity of psoriasis is highlighted by its increased mortality, with cardiovascular diseases contributing the highest excess risk. From a scientific point of view, psoriasis has to be considered a systemic inflammatory condition, as blood biomarkers of inflammation are elevated and imaging techniques document sites of inflammation beyond the skin. While the association of psoriasis with cardiovascular diseases is now widely accepted, causes and consequences of this association are controversially discussed. This review comments on epidemiologic, genetic, and mechanistic studies that analyzed the relation between psoriasis and cardiovascular comorbidity. The hypothesis of psoriasis potentially being an independent cardiovascular risk factor, driving atherosclerosis via inflammation-induced endothelial dysfunction, will be discussed. Finally, consequences for the management of psoriasis with the objective to reduce the patients’ excess cardiovascular risk will be pointed out.